Personality Of Volleyball Athletes Faculty Student Activity Unit (UKMF) PGRI University Of Palembang - Mutiara Fajar; Siti Ayu risma Putri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to determine the personality of the Volleyball athletes at the Faculty Student Activity Unit (UKMF) PGRI Palembang University. As seen from the emotional stability, discipline, and self-confidence. This research method is descriptive research. The instrument used to collect the data was a questionnaire using a Likert scale which was given to 34 volleyball athletes in the faculty student activity unit (UKMF) of PGRI Palembang University with total sampling technique. The results showed that the personality of the Volleyball athlete in the faculty student activity unit (UKMF) of PGRI Palembang University, seen from emotional stability, discipline, and self-confidence, which was at a percentage of 79% and was in good criteria.